EDUKASI PENDERITA STROKE DI PUSKESMAS NOGOSARI BOYOLALI : (Fisioterapi sebagai Bagian Inti dalam Edukasi Pasien Stroke) - Susilo, Taufik Eko; Wulandari, Puput; Khoirunnisa, Asty; Dharmawan, Yan Ari Tya; Marshela, Ajeng; Sudaryanto, Wahyu Tri (Transpublika Publisher, 2023)
This study focuses on the implementation of stroke education at Nogosari Boyolali Community Health Center, with an emphasis on the pivotal role of physiotherapy in the educational process. Stroke education is a crucial aspect of post-stroke care, aiming to empower patients with knowledge and skills for effective self-management. This research explores the integrated approach of physiotherapy within the educational framework, highlighting its significance in enhancing patients' physical and cognitive functions. Through a comprehensive review of educational materials and interactive sessions, patients are equipped with tailored strategies for daily living and stroke prevention. The study also evaluates the impact of this holistic education on patients' independence and overall prognosis. The findings underscore the indispensable role of physiotherapists in stroke education, emphasizing their contributions to the multidisciplinary care team. This research provides valuable insights for optimizing stroke education programs in community health settings, ultimately improving the quality of life for stroke survivors.